Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd008783.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac with or without an antiemetic for acute migraine headaches in adults

Abstract: Background Migraine is a common, disabling condition and a burden for the individual, health services and society. Many sufferers choose not to, or are unable to, seek professional help and rely on over-the-counter (OTC) analgesics. Diclofenac is an established analgesic, and new formulations using the potassium or epolamine salts, which can be dissolved in water, have been developed for rapid absorption, which may be beneficial in acute migraine. Co-therapy with an antiemetic should help to reduce the nausea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…A Cochrane meta-analysis showed that oral forms of paracetamol,3 ibuprofen,4 diclofenac5 and sumatriptan, that seem to be more expensive than simple analgesics,6 are effective in treating the migraine attack. However, few studies have examined the effectiveness of parenteral drugs in migraine attacks.…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane meta-analysis showed that oral forms of paracetamol,3 ibuprofen,4 diclofenac5 and sumatriptan, that seem to be more expensive than simple analgesics,6 are effective in treating the migraine attack. However, few studies have examined the effectiveness of parenteral drugs in migraine attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Among the articles found by this search, only articles on RCTs of acute migraine treatment were searched by personal evaluation of abstract and methods section for results beyond 2 hours. In addition, articles with results beyond 2 hours were retrieved by hand search of reference lists of meta-analyses 4,5,13,14 and Cochrane reviews 6,7,[15][16][17][18][19] on drugs for migraine attack treatment. For the main analysis, which was the evaluation of time-effect curves of oral drugs (Table 1), we included *Rescue medication used in oral randomised controlled trials presented in this and other tables and in the text is more frequent in the placebo group.…”
Section: Methodsmentioning
confidence: 99%
“…Intranasal zolmitriptan 5 mg TG, 23% (95% CI: 20%-26%) 110,111 Soluble diclofenac 50 mg TG, 14% (95% CI: 9%-18%) 17 Nasal-delivered sumatriptan powder 22 mg TG, 17% (95% CI: 5%-28%) 112 Orally inhaled dihydroergotamine 1 mg TG, 18% (95% CI: 12%-23%) 31,33 Transdermal patch with sumatriptan TG, 9% (95% CI: 3%-15%) 113…”
Section: Section 2 New Administration Routes For Current Drugsmentioning
confidence: 99%
“…are quite variable. [3][4][5][6][7][8] Peripheral nerve blocks are an alternative to drugs for primary headaches. Local anesthetics and/or steroidal injections are used for this purpose.…”
mentioning
confidence: 99%